How to Operate Word: Moving an Article Draft into A Journal Template - Dwi Novia Al Husaeni; Asep Bayu Dani Nandiyanto (Universitas Pendidikan Indonesia (UPI), 2023)
Submitting papers to journals is an activity that is often carried out by authors. Before the submission process, there is one step that must be carried out by the author, namely the article template. Article templates are an activity to customize our writing to match the journal template. The purpose of this study is to demonstrate step-by-step the creation of templates for articles that will be submitted to journals. The step-by-step analysis is provided to make it easier for first-time authors to do journal templates using Microsoft Word. This research makes it possible to make it easy to do article templates by utilizing the Microsoft Word application. Ms. Application Word is used because it is free and can be used offline. As a practical example, we did an article template into the ASEAN Journal of Science and Engineering (AJSE) template. How to set the format for tables, images, paragraphs, title paragraphs, and copy and paste articles is discussed in detail in this study.